The case for Christ [videorecording (DVD)] - Vogel, Mike; Christensen, Erika, 1982-; Dunaway, Faye; Strobel, Lee, 1952- (Universal Pictures Home Entertainment, 2017)
Based on the true story of an award-winning journalist who, working to disprove the newfound Christian faith of his wife, begins chasing down the biggest story of all time, with unexpected, life-altering results.